1995
DOI: 10.1093/eurheartj/16.suppl_g.10
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and risk stratification after myocardial infarction

Abstract: In order to assess prognosis after myocardial infarction, various methods have been used: estimation of ejection fraction, Holter monitoring, detection of ventricular late potentials using signal-averaging techniques, programmed ventricular stimulation of the heart to test the inducibility of ventricular tachyarrhythmias, and parameters that assess heart rate variability. Left ventricular dysfunction is the major determinant for prognosis after myocardial infarction, but left ventricular end-systolic volume ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…These findings were consistently reproduced in subsequent reports from numerous other authors [9,10] and more definitively in the large Autonomic Tone and Reflexes After Myocardial Infarction (ATRAMI) trial [11]. These trials conclusively demonstrated that not only was the predictive value of HRV independent, but also incremental to factors such as left ventricular ejection fraction (EF), presence of ventricular ectopy, and presence of late potentials [12][13][14]. The other established use of HRV has been in the evaluation of autonomic neuropathy in diabetic patients [15].…”
Section: Established Clinical Usessupporting
confidence: 61%
“…These findings were consistently reproduced in subsequent reports from numerous other authors [9,10] and more definitively in the large Autonomic Tone and Reflexes After Myocardial Infarction (ATRAMI) trial [11]. These trials conclusively demonstrated that not only was the predictive value of HRV independent, but also incremental to factors such as left ventricular ejection fraction (EF), presence of ventricular ectopy, and presence of late potentials [12][13][14]. The other established use of HRV has been in the evaluation of autonomic neuropathy in diabetic patients [15].…”
Section: Established Clinical Usessupporting
confidence: 61%
“…They were enrolled from a larger population, most of whom were deemed ineligible due to preserved left ventricular function, a serious comorbid illness, or an inability or unwillingness to undergo serial testing. (17,22), followed by a 20-to 30-min high-resolution digital electrocardiographic (ECG) recording, from which signal-averaged QRS width (18) and Holter TWA were measured (13). Participants then underwent phenylephrine-induced baroreflex sensitivity (BRS) testing (9).…”
Section: Recruitmentmentioning
confidence: 99%
“…Combining multiple measures of autonomic tone (15,16) or combining multiple measures of electrical substrate (17) has not been shown to improve diagnostic accuracy. Combining measures of autonomic tone with measures of electrical substrate may enhance risk assessment (15,18), but this strategy remains unproven in the era of contemporary post-MI management (19).…”
mentioning
confidence: 99%
“…Given that a cardiac arrest likely requires a confluence of abnormalities, combining noninvasive test results to enhance risk prediction has intuitive appeal (70,71). Table 3 summarizes several recent studies that have combined noninvasive tests to enhance risk prediction.…”
Section: Combining Noninvasive Parameters To Enhance Risk Assessmentmentioning
confidence: 99%